2014
DOI: 10.1007/s00125-014-3392-8
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic P2Y1 receptors take centre stage in autocrine stimulation of human beta cells

Abstract: Insulin secretory vesicles contain high concentrations of adenine nucleotides, which are co-released with insulin during exocytosis. There is strong evidence that ATP and ADP serve as autocrine messengers in pancreatic beta cells, but the functional effects and detailed mechanisms of action are under debate. In this issue of Diabetologia, Khan and colleagues (DOI: 10.1007/s00125-014-3368-8) present the results of their study of autocrine purinergic signalling in isolated human beta cells. Using a combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…ATP has been previously identified among para‐ and autocrine signaling factors in the extracellular space of rodent and human pancreatic islets to act on P2 purinergic receptors (Jacques‐Silva et al, 2010 ; Tengholm, 2014 ). Effects of autocrine ATP as an extracellular signaling factor were investigated on the pancreatic cell lines MIN6 (murine) (Ishihara et al, 1993 ) and 1.1B4 (human) (McCluskey et al, 2011 ) as well as on isolated mouse primary β‐cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ATP has been previously identified among para‐ and autocrine signaling factors in the extracellular space of rodent and human pancreatic islets to act on P2 purinergic receptors (Jacques‐Silva et al, 2010 ; Tengholm, 2014 ). Effects of autocrine ATP as an extracellular signaling factor were investigated on the pancreatic cell lines MIN6 (murine) (Ishihara et al, 1993 ) and 1.1B4 (human) (McCluskey et al, 2011 ) as well as on isolated mouse primary β‐cells.…”
Section: Resultsmentioning
confidence: 99%
“…Acting on G‐protein‐coupled P2Y receptors and ionotropic P2X receptors, ATP increases [Ca 2+ ] i by stimulating InsP 3 ‐mediated Ca 2+ release from the endoplasmic reticulum (ER) (Khan et al, 2014 ) or by increased Ca 2+ influx into the cell. External ATP was suggested to promote intra‐ and inter‐islet propagation of [Ca 2+ ] i oscillations in a para‐, and autocrine fashion within the enclosed pancreatic islet (Burnstock & Novak, 2013 ; Petit et al, 1998 ; Tengholm, 2014 ). Thereby, ATP entrains pancreatic islets into a common rhythm, to make islets sensitive to fluctuating glucose levels and to ensure rapid and adapted glucose responsiveness (Grapengiesser et al, 2004 , 2005 ; Hellman et al, 2004 ; Jacques‐Silva et al, 2010 ; Petit et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of adenine nucleotides on β cells are pleiotropic and involve the action of several purinergic receptors (reviewed in Refs. 48 , 49 ). Recent work in human β cells confirmed that P2Y 1 receptors mediate autocrine stimulation of insulin secretion ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, activation of P2X3 and P2Y13 also exerted deleterious effects on insulin secretion in pancreatic β cells ( Petit et al, 2009 ). In contrast, P2Y1 can be activated by Ca 2+ -induced ATP release to depolarize cell membrane and amplify Ca 2+ signals, augmenting insulin secretion in pancreatic β cells ( Hellman et al, 2004 ; Tengholm, 2014 ).…”
Section: Reduced Atp Production and Dysfunction Of Atp Signaling Asso...mentioning
confidence: 99%